Pembuatan briket dari kombinasi kulit kacang tanah (arachis hypogaea l.) dan kulit kacang pistachio pistacia vera l.) dengan tepung tapioka sebagai perekat - Rahmadhani, Dava Ariesta; Kusumayanti, Heny (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Energy is one of humanity's basic needs; however, the reserves of non-renewable conventional fuels are depleting, and the associated costs are rising due to the heavy reliance on fossil fuels. Innovative solutions are required to produce alternative energy sources that are practical, economical, and efficient. Briquettes are one such alternative fuel derived from various biomass materials. This study aims to determine the optimal conditions for producing briquettes using a combination of peanut shells and pistachio shells bound with tapioca flour. The briquettes produced were tested for moisture content, ash content, burning duration, density, and burning rate. The results identified Sample 5 as the best formulation, consisting of 32 grams of peanut shells, 32 grams of pistachio shells, and 5% tapioca flour. This sample exhibited a moisture content of 4.9%, ash content of 6.8%, density of 0.496 g/cm³, a burning duration of 35 minutes, and a burning rate of 3.28 grams/minute. The study also concluded that the binder percentage significantly influences the quality of the briquettes produced.